2011
DOI: 10.1039/c0jm04583g
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, self-assembly and field-effect transistor properties of anti- and syn- thienoacene isomers

Abstract: The relationships between the molecular structure, self-assembly and charge transport properties of two fused-ring thienoacene isomers, a sickle-like syn isomer and a linear anti isomer, were studied from both an experimental and a theoretical perspective. Under the same self-assembly conditions, the syn isomer formed one-dimensional (1D) micro-and nanoribbons, while the anti isomer formed two-dimensional (2D) nanoplates (all were single crystals). The differences were assigned to the change in intermolecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…2) It is still controversial to conclude which configuration ( anti ‐/ syn ‐) has better performance. The results from some research groups (Hu et al., Tokito et al., Jurchescu et al., Mamada et al., Takimiya et al., and Zhao et al …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…2) It is still controversial to conclude which configuration ( anti ‐/ syn ‐) has better performance. The results from some research groups (Hu et al., Tokito et al., Jurchescu et al., Mamada et al., Takimiya et al., and Zhao et al …”
Section: Figurementioning
confidence: 99%
“…We have further performed an in‐depth theoretical study into fundamentals factors, especially the isomer geometry in affecting charge transport properties,,, based on density functional theory (DFT) calculations and a 1D polaron transport model that takes both band‐like and hopping transport into account. The main parameters for charge transport include hole transfer integrals ( t h ) and hole polaron binding energies (Epolh ), in which t h is closely related to the molecular packing and intermolecular distances while Epolh is closely related to molecular geometry.…”
Section: Figurementioning
confidence: 99%
“…Recently, some research works have focused on the structural control of isomers. 23,36 Our group fabricated well-dened spheres, wires, and cubes from three isomeric precursors, o-, mand p-bis-(iminopyrrole) benzene. 37 Although the three isomeric molecules present similar strong multiple hydrogen-bonding interactions for molecular aggregation, distinctly shaped nanostructures (spheres, wires, and cubes) were obtained, as displayed in Fig.…”
Section: Structural Control With Molecular Designmentioning
confidence: 99%
“…It has been found that the syn / anti configuration of the molecular backbone could significantly influence the molecular packing and charge mobility of organic semiconductors used as organic field‐effect transistors . For some molecular structures, syn isomers exhibit higher charge mobility,, whereas anti isomers show better performance in other cases . Therefore, the syn / anti isomerization of the configuration of FREAs would also affect the molecular packing and charge transport, and thus the photovoltaic performance.…”
Section: Introductionmentioning
confidence: 99%